Constructing Education in Sustaining Islamic Values Based on Local Culture Among the Fisherfolk Community - Subekti, Sadin; Hilmy, Masdar (Al-Hayat Al-Istiqomah Foundation collab with Letiges, 2024)
This research aims to explore and develop Islamic education rooted in local culture among the fishing community on the North Coast of Gresik. The research method used is a qualitative approach with an ethnographic type. The data collection techniques include participant observation, in-depth interviews and documentation studies. This study adopts the taxonomic analysis developed by Spradley, which provides for taxonomic, semantic, componential, and cultural theme analyses. The data validation technique uses triangulation. Research findings show that constructing Islamic values ??with local traditions in education among fishing communities can strengthen their religious and cultural identity and enrich their educational experience. This research also found that active participation and awareness of the fishing community regarding the urgency of Islamic education can increase their involvement in the learning process. This research argues that an Islamic education approach based on local culture will be able to encourage strengthening the relationship between the younger generation and the traditions and values ??inherited from their ancestors. The limitation of this research is that it does not yet explain the challenges of the digital revolution in the local cultural context. The main contribution of this research is to provide a theoretical and practical basis for the development of Islamic education that is more inclusive and relevant to the local social and cultural context by emphasizing local wisdom as a source of strength and sustainability of Islamic education.